(untitled) (Al-Aasar, 2026)
Accent bias remains one of the most consequential yet least legally protected forms of language-based discrimination in global higher education and workplace settings. This conceptual paper synthesises peer-reviewed scholarship published between 2019 and 2026 to clarify how listeners evaluate South Asian English speakers and to distinguish judgments of understanding from judgments of social worth. Drawing on an integrative review of empirical and theoretical work in applied linguistics, sociolinguistics, and organisational psychology, the paper separates four frequently conflated constructs—intelligibility, comprehensibility, accentedness, and social attitude—and maps how each is shaped by listener familiarity, exposure to World Englishes, racialised expectation, gender, and the ideology of native-speakerism. The synthesis shows that a noticeable accent does not reliably reduce actual understanding, yet standard-accented speakers are consistently favoured in hiring and instructional evaluation, with stereotypes of competence rather than comprehension difficulty driving much of the disadvantage. South Asian Englishes emerge as systematically under-represented in perception research, and the limited evidence that does exist relies heavily on non-South-Asian listeners, leaving the perceptions of and toward South Asian speakers in their own institutional contexts largely unexamined. The paper argues for decoupling comprehension from evaluation in pronunciation pedagogy, assessment, and recruitment, and offers a conceptual framework and research agenda for fairer treatment of South Asian English in education and employment.